Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 5.2 Answers

  • Page ID
    28907
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(y=c_{1}e^{-6x}+c_{2}e^{x}\)

    2. \(y=e^{2x}(c_{1}\cos x+c_{2}\sin x)\)

    3. \(y=c_{1}e^{-7x}+c_{2}e^{-x}\)

    4. \(y=e^{2x}(c_{1}+c_{2}x)\)

    5. \(y=e^{-x}(c_{1}\cos 3x+c_{2}\sin 3x)\)

    6. \(y=e^{-3x}(c_{1}\cos x+c_{2}\sin x)\)

    7. \(y=e^{4x}(c_{1}+c_{2}x)\)

    8. \(y=c_{1}+c_{2}e^{-x}\)

    9. \(y=e^{x}(c_{1}\cos\sqrt{2}x+c_{2}\sin\sqrt{2}x)\)

    10. \(y=e^{-3x}(c_{1}\cos 2x+c_{2}\sin 2x)\)

    11. \(y=e^{-x/2}\left(c_{1}\cos\frac{3x}{2}+c_{2}\sin\frac{3x}{2} \right)\)

    12. \(y=c_{1}e^{-x/5}+c_{2}e^{x/2}\)

    13. \(y = e ^{-7x} (2 \cos x − 3 \sin x)\)

    14. \(y=4e^{x/2}+6e^{-x/3}\)

    15. \(y=3e^{x/3}-4e^{-x/2}\)

    16. \(y=\frac{e^{-x/2}}{3}+\frac{3e^{3x/2}}{4}\)

    17. \(y=e^{3x/2}(3-2x)\)

    18. \(y=3^{-4x}-4e^{-3x}\)

    19. \(y=2xe^{3x}\)

    20. \(y=e^{x/6}(3+2x)\)

    21. \(y=e^{-2x}\left(3\cos\sqrt{6}x+\frac{2\sqrt{6}}{3}\sin\sqrt{6}x \right)\)

    23. \(y=2e^{-(x-1)}-3e^{-2(x-1)}\)

    24. \(y=\frac{1}{3}e^{-(x-2)}-\frac{2}{3}e^{7(x-2)}\)

    25. \(y=e^{7(x-1)}(2-3(x-1))\)

    26. \(y=e^{-(x-2)/3}(2-4(x-2))\)

    27. \(y=2\cos\frac{2}{3}\left(x-\frac{\pi }{4} \right) -3\sin\frac{2}{3}\left(x-\frac{\pi }{4} \right)\)

    28. \(y=2\cos\sqrt{3}\left( x-\frac{\pi }{3}\right)-\frac{1}{\sqrt{3}}\sin\sqrt{3}\left(x-\frac{\pi }{3} \right)\) 

    30. \(y=\frac{k_{0}}{r_{2}-r_{1}}\left(r_{2}e^{r_{1}(x-x_{0})}-r_{1}e^{r_{2}(x-x_{0})}  \right) +\frac{k_{1}}{r_{2}-r_{1}}\left(e^{r_{2}(x-x_{0})}-e^{r_{1}(x-x_{0})} \right)\)

    31. \(y=e^{r_{1}(x-x_{0})}[k_{0}+(k_{1}-r_{1}k_{0})(x-x_{0})]\)

    32. \(y=e^{\lambda (x-x_{0})}\left[ k_{0}\cos\omega (x-x_{0})+\left(\frac{k_{1}-\lambda k_{0}}{\omega } \right)\sin\omega (x-x_{0}) \right]\)